Efficacy of Calcined Layered Double Hydroxide Clays in the Remediation of Phenol from Wastewater - Tichapondwa, Shepherd Masimba (University of Pretoria, 2021)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2021.